A community-based approach to identifying defence of microalgae against protozoan grazing. (3rd March 2017) - Wang, Zheng; Xu, Guangjian; Zhao, Lu; Gao, Yangyang; Al Mamun, Abdullah; Xu, Henglong
Abstract : It has increasingly been recognized that defence of microalgae against predator grazing is a passive response to increase algal population density by excreting chemicals with a change in physical properties. As common biological pollutants in the cultivation of the microalgae, the community-based method was used to identify the ability of two microalgae, Chlorella sp. and Nannochloropsis oceanica, to defend against protozoan grazing. Mature protozoan samples with 14-day age were collected, using microscopy glass slides, in coastal waters of the Yellow Sea, northern China. For both microalgae, a gradient of concentrations was designed as 10 0 (control), 10 4, 10 5, 10 6 and 10 7 cell ml −1, respectively. Results showed that both test algal species represented strong defence effects on protozoan grazing, especially at high density levels. Species richness, abundance and taxonomic distinctness of the protozoan assemblages showed a sharp decrease at high concentration level (10 7 cell ml −1 ) of both algae. A significant variation in protozoan community structures was found to be driven by the gradient of the algal concentrations. The paired taxonomic distinctness indices of the protozoan communities showed an increasing trend of departure from the expected taxonomic pattern with increase of algal concentrations. Based on the results, we suggest that the community-based bioassay might be used as a feasible tool for identifying defence against protozoan grazing of microalgae.